Tailoring Bi-Te based nanomaterials by electrodeposition: Morphology and crystalline structure. (15th March 2017) - Proenca, M.P.; Rosmaninho, M.; Resende, P.M.; Sousa, C.T.; Ventura, J.; Araújo, J.P.; Fernandes, L.; Tavares, P.B.; Pereira, A.M.
Abstract: Bi2 Te3 is the most commonly used thermoelectric material in modern solid-state refrigerators and power generators based on this basic principle. Due to predictions of significant improvements in their efficiency by using nanostructured materials, a thorough study on thin films and nanowires deposited by the electrodeposition method are here presented. The study of the deposition applied potential effect on the morphology, stoichiometry and crystallinity of both thin films and nanowires has been conducted. The morphology and stoichiometry was found to highly depend on the deposition potential, where by increasing it one was able to accurately control the Te% content of the deposits. X-ray diffraction measurements have shown the presence of a strong relation between the material's crystallinity and the deposition potential, where samples ranged from monocrystalline, at very low potentials, to almost completely amorphous, at high potentials. Finally, nanowire diameters were seen to diminish with the applied potential, in conjunction with the general array. Graphical abstract: Highlights: Tailoring of microstructure of Bi2 Te3 thin films Fine tune of pore filling Bi2 Te3 nanowires in alumina template Control crystallinity through electrodeposition method Stoichiometric adjust of Bi2 Te3 using different voltages